2014
DOI: 10.1021/jp409541u
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Excited State Electron Transfer at Liquid/Liquid Interfaces

Abstract: Abstract:Several aspects of the photoinduced electron transfer (ET) reaction between coumarin 314 (C314) and N,N-dimethylaniline (DMA) at the water/DMA interface are investigated by molecular dynamics simulations. New DMA and water/DMA potential energy surfaces are developed and used to characterize the neat water/DMA interface.The adsorption free energy, the rotational dynamics and the solvation dynamics of C314 at the liquid/liquid interface are investigated and are generally in reasonable agreement with ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 131 publications
1
7
0
Order By: Relevance
“…Molecular dynamics calculations of the reorganization free energy and solvation dynamics in the C314 at water/DMA system gave results in agreement with the experiments (114). The calculations suggest that the rate enhancement at the interface relative to the bulk is likely due to faster solvation dynamics at the interface.…”
Section: Photoinduced Et At Liquid/liquid Interfacessupporting
confidence: 80%
“…Molecular dynamics calculations of the reorganization free energy and solvation dynamics in the C314 at water/DMA system gave results in agreement with the experiments (114). The calculations suggest that the rate enhancement at the interface relative to the bulk is likely due to faster solvation dynamics at the interface.…”
Section: Photoinduced Et At Liquid/liquid Interfacessupporting
confidence: 80%
“…Electron transfer at interfaces has a long history that is justified by a broad applicability ranging from electrochemistry to biology and solar energy technologies (see ref for a recent review on these processes). Likewise, in bulk solution, Marcus theory can account for the observed solvent effects on electron transfer at interfaces. , A study of photoinduced electron transfer at water/dimethylaniline interfaces , concluded that the interfacial processes are faster than the bulk processes, possibly due to faster solvation dynamics at the interface . The stability of solvated electrons at aqueous interfaces has also been studied, and simulations have predicted that the water surface electron affinity is ∼0.6 eV higher than in the bulk, and that the conduction band edge is deeper in energy.…”
Section: Discussionmentioning
confidence: 99%
“…203,204 A study of photoinduced electron transfer at water/dimethylaniline interfaces 205,206 concluded that the interfacial processes are faster than the bulk processes, possibly due to faster solvation dynamics at the interface. 207 The stability of solvated electrons at aqueous interfaces has also been studied, [208][209][210] and simulations have predicted that the water surface electron affinity is ~0.6 eV higher than in the bulk, and that the conduction band edge is deeper in energy. Electron transfer is also relevant in pcet mechanisms and can be significantly affected by aqueous solvation, as shown for the 3 SO2 + H2O reaction 116 and the H2CO + HO2 reaction.…”
Section: Scheme 1 Factors Affecting Photo-induced Reactions At the Ai...mentioning
confidence: 99%
“…So far, X-ray reflectivity and molecular dynamics have not been applied to study electron transfer reactions, but these techniques would help to elucidate how the reactions actually happen. Recently, molecular dynamics simulations have been employed to study photoinduced electron transfer between coumarin 314 and N,N-dimethylaniline [32]. Spectroscopic techniques such as surface second harmonic generation [33], potential modulated fluorescence [29] etc.…”
Section: Graphical Abstract 1 Introductionmentioning
confidence: 99%